Epidemiology of neonatal infections in hospitals of Nepal: evidence from a large- scale study - Shyam Sundar Budhathoki; Avinash K. Sunny; Pragya Gautam Paudel; Jeevan Thapa; Lila Bahadur Basnet; Sandeepa Karki; Rejina Gurung; Prajwal Paudel; Ashish KC (BMC, 2020)
Abstract Background Every year, neonatal infections account for approximately 750,000 neonatal deaths globally. It is the third major cause of neonatal death, globally and in Nepal. There is a paucity of data on clinical aetiology and outcomes of neonatal infection in Nepal. This paper aims to assess the incidence and risk factors of neonatal infection in babies born in public hospitals of Nepal. Methods This is a prospective cohort study conducted for a period of 14 months, nested within a large-scale cluster randomized control trial which evaluated the Helping Babies Breathe Quality Improvement package in 12 public hospitals in Nepal. All the mothers who consented to participate within the study and delivered in these hospitals were included in the analysis. All neonates admitted into the sick newborn care unit weighing > 1500 g or/and 32 weeks or more gestation with clinical signs of infection or positive septic screening were taken as cases and those that did not have an infection were the comparison group. Bivariate and multi-variate analysis of socio-demographic, maternal, obstetric and neonatal characteristics of case and comparison group were conducted to assess risk factors associated with neonatal infection. Results The overall incidence of neonatal infection was 7.3 per 1000 live births. Babies who were born to first time mothers were at 64% higher risk of having infection (aOR-1.64, 95% CI, 1.30-2.06, p-value< 0.001). Babies born to mothers who had no antenatal check-up had more than three-fold risk of infection (aOR-3.45, 95% CI, 1.82-6.56, p-value< 0.001). Babies born through caesarean section had more than two-fold risk (aOR-2.06, 95% CI, 1.48-2.87, p-value< 0.001) and babies with birth asphyxia had more than three-fold risk for infection (aOR-3.51, 95% CI, 1.71-7.20, p-value = 0.001). Conclusion Antepartum factors, such as antenatal care attendance, and intrapartum factors such as mode of delivery and birth asphyxia, were risk factors for neonatal infections. These findings highlight the importance of ANC visits and the need for proper care during resuscitation in babies with birth asphyxia.